The nature of the job duties of the Diyala Brigade administrators and their economic, social and service achievements (1927-1932AD) (Journal of the College of Basic Education, 2023)
The research deals with the nature of the functional tasks of the administrators of the Diyala District and their achievements in the economic, social and service aspects in the period from (January 26, 1927 - March 11, 1932 AD). The year (1927 AD) was determined as the beginning of the research, as it represents the receipt of the governorship, Mahmoud Nadim al-Tabaqjali, the governorship of the brigade. Social, economic and other services in the Diyala district, especially addressing agricultural problems and land ownership, river floods, watering agricultural crops, improving educational and municipal services and delivering electricity to the people, as well as enriching the Iraqi library with academic productions that shed light on the history of (the administrators) in the various development work of the Diyala district in search duration. The research material was distributed into two sections, an introduction and a conclusion. The first topic showed (the role of the Diyala Brigade administrators in developing the economic reality in Diyala 1927-1930 AD), and the second topic dealt with: (the role of the Diyala District administrators in developing the economic, social and service reality in Diyala 1930-1932 AD). The researcher adopted the descriptive historical approach with an analysis of the most important actions of the administrators and their achievements during the research period. The research was based on a lot of Arabic and Arabized sources and references. The research reached several results, including: the distinction of those who held the position of (administrator) of the Diyala Brigade in the period (1927-1932 AD) because they were capable administrative employees, and the issuance of some laws and regulations, especially the Brigades Administration Law No. (58) of (1927 AD) and its amendments, had helped The governors of the district enabled them to implement many social, economic and service reforms in the Diyala district, such as addressing the administrative divisions and administrative boundaries of the municipalities of the districts and sub-districts in the district, and paying attention to the agricultural aspect due to the fact that the district is one of the agricultural brigades with diverse crops such as wheat, barley, vegetables, etc., and the efforts of the Diyala district administrators continued to address Many tribal heads and tribal sheikhs in Diyala have benefited from these laws and procedures carried out by the district governor, as large areas of land were registered in the names of clan sheikhs, and the peasants who used to constitute the majority in Diyala society were deprived of it. At that time, which doubled the agricultural holdings of the sheikhs and increased their social power and political influence, and then their favour. At the commanding officer. The researcher pointed out that the British administration exploited the issue of agricultural properties to consolidate its influence and control over Iraq, including the Diyala District at that time, and the administrators of the Diyala District addressed the problem of watering the farms due to the lack of water and the high level of the farmers’ lands, so they asked the central government to construct a fixed dam on the Diyala River, and it was accomplished The project was in the year (1929 AD), in addition to the interest of the administrators in dealing with the problems of flooding rivers in Diyala, and the great negative effects they leave on the lives of farmers. In addition to developing the electricity service in the brigade. As for the health conditions in the Diyala district, there was no clear change during the research period. While the conditions of education witnessed an aspect of the interest of the administrators by opening many primary schools for males and females in the district in the period (1930-1932 AD). The researcher pointed out the most important reasons for the failure of some of the district's administrators to fulfill their administrative duties, and their lack of urban and service achievements due to the short period of their tenure for reasons related to the policy of the Ministry of Interior and the Iraqi government at the time.